2015
DOI: 10.22621/cfn.v129i2.1697
|View full text |Cite
|
Sign up to set email alerts
|

Apparent extirpation of prey fish communities following the introduction of Northern Pike (<em>Esox lucius</em>)

Abstract: We examined the long-term effects on prey fish communities of introducing Northern Pike (Esox lucius), a top predator fish, into small, Boreal Shield lakes lacking natural piscivore populations. During 1987–1994, Northern Pike were introduced into Lakes 110, 221, and 227 in the Experimental Lakes Area in northwestern Ontario, Canada. In Lake 227, prey fish were undetectable three years after the addition of Northern Pike. Although Northern Pike were removed from the lake by 1996, multiple independent visual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The presence of large piscivorous perch is also known to hinder the reestablishment of roach, unless coexistence of perch and roach is mediated by the presence of pike (Persson, De Roos, & Bystrom, 2006). Monitoring small lakes after the introduction of perch or pike revealed rapid extinction (within <50 years) of nine-spined and three-spined sticklebacks (Englund et al, 2009) and small cyprinidae (Nicholson, Rennie, & Mills, 2015). The fact that piscivores enter the best models only in combination with depth clearly suggests that their impact on prey species is sufficiently strong to induce extinction in deep lakes, but this outcome is less likely in shallow lakes confirming the complex relationships between piscivores, preys and depth already emphasized in a previous study of the very same system (Englund et al, 2009).…”
Section: Piscivorous Effectmentioning
confidence: 99%
“…The presence of large piscivorous perch is also known to hinder the reestablishment of roach, unless coexistence of perch and roach is mediated by the presence of pike (Persson, De Roos, & Bystrom, 2006). Monitoring small lakes after the introduction of perch or pike revealed rapid extinction (within <50 years) of nine-spined and three-spined sticklebacks (Englund et al, 2009) and small cyprinidae (Nicholson, Rennie, & Mills, 2015). The fact that piscivores enter the best models only in combination with depth clearly suggests that their impact on prey species is sufficiently strong to induce extinction in deep lakes, but this outcome is less likely in shallow lakes confirming the complex relationships between piscivores, preys and depth already emphasized in a previous study of the very same system (Englund et al, 2009).…”
Section: Piscivorous Effectmentioning
confidence: 99%
“…Specifically, we combined habitat suitability modelling, estimates of connectivity and human transport that drive species introductions, and Bayesian networks to assess the vulnerability of five Pacific salmon species confronted with a novel top predator. Our approach has broad application both inside and outside of Alaska as pike have been introduced and deemed ‘invasive’ throughout much of their non-native distribution and are currently threatening the persistence of a variety of native fishes (Western United States: [ 67 ], Canada: [ 68 ], Spain: [ 69 ], and elsewhere in the Mediterranean: [ 70 ]). In the face of increasing invasions in freshwaters, assessments such as ours provide managers with quantitative methods to assess the impacts of species introductions quickly and efficiently over large geographic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous field studies have reported such negative associations, particularly, between top predators and prey species. For example, experiments introducing predatory fishes resulted in decline of minnow species due to direct consumption (Findlay et al., 2000; Mittelbach et al., 1995; Nicholson et al., 2015) or emigration to refugia from predation (e.g. outflow channels; He & Kitchell, 1990).…”
Section: Discussionmentioning
confidence: 99%